Scientific Research Methodology in Exploratory Qualitative Studies: Methods, Approaches, and Tools - El-Yazidi, Reda (Journal of Humanities & Social Sciences, 2025)
Researchers and students, especially in the humanities and social sciences, need to conduct qualitative research and studies and write them in a way that respects the standards of scientific rigor and accepted scientific research methodologies. This study, based on a literature review of qualitative research methodology, serves as a guide for researchers who are interested to conduct exploratory qualitative studies, with a particular focus on content analysis as a method of qualitative research. Thus, this study highlighted the basic principles underlying qualitative research and studies, including the epistemological paradigm to which it belongs and the inductive logic that drives it, followed by the practical aspects and stages of conducting qualitative research, such as choosing appropriate methods according to the research goal and issue, designing sampling strategies, and using effective data collection tools. The study also highlighted the important role of systematic organization and analysis in transforming raw data into meaning insights, while introducing some qualitative analysis programs to enhance accuracy and efficiency in data processing and analysis. The limitations of the study is that it did not delve into the technical complexities of qualitative analysis software and did not focus on the possibility of qualitative research incorporating mixed methods to enhance the validity and generality of the results, thus forming one of the research paths that can be explored in future studies and research.
Keywords: Research methodology; exploratory qualitative study; epistemological model; inductive reasoning; sample; content analysis